Understanding Fertility Trends of Assam: A District-Level Spatial Analysis Through K-Means Clustering - Baruah, Chayanika; Talukdar, Ruma; Sarma, Saurav (National Journal of Community Medicine, 2025)
Background: Understanding regional fertility patterns is crucial for effective demographic planning and policy formulation. This study estimates the district-level Age-Specific Fertility Rate (ASFR) for Assam and employs cluster analysis to classify the districts of Assam based on their current fertility patterns. The cluster analysis identifies distinct groups with similar fertility characteristics, providing insights into regional variations and demographic transitions across the region. The findings highlight significant heterogeneity in fertility levels within Assam, reflecting diverse socio-economic and cultural influences. Methods: The K-means clustering technique has been used to group the districts of Assam into distinct clusters. Results: It was found that based on the calculated single-year age-specific fertility rates, the districts of Assam can be divided into two distinct and non-overlapping clusters. A further comparison of some socio-demographic factors between the two clusters revealed that Cluster 1 (Low Fertility Zone) had higher education levels and a greater proportion of Assamese-speaking women compared to Cluster 2 (High Fertility Zone). Conclusion: The districts of Assam, India, can be divided into two distinct groups with significantly different fertility patterns and demographics of the mothers. These findings can guide targeted reproductive health interventions in high-fertility districts.